Synthesis of Nanostructured sawdust-BF3: An efficient reagent for synthesis of 2,3,5-substituted-2H-pyrazole derivatives - Molaei, Hamidreza; Sadeghi, Bahareh; Moslemin, Mohamadhosaine (Ciência e Natura, 2015)
Nanostructured sawdust-BF3 has been prepared and shown to efficiently catalyse the one-pot reaction of 1,3-diketones and hydrazines under solvent-free conditions, to afford the corresponding 2,3,5-substituted-2H-pyrazole derivatives in excellent yields.